Analisis Perhitungan Jembatan Gelagar I pada Jembatan Jalan Raya dan Jembatan Kereta Api - Irpan Hidayat (Bina Nusantara University, 2013)
The bridge is a means of connecting roads which is disconnected by barriers of the river, valley, sea, road or railway. Classified by functionality, bridges can be divided into highway bridge and railroad bridge. This study discusses whether the use of I-girder with 210 m height can be used on highway bridges and railway bridges. A comparison is done on the analysis of bridge structure calculation of 50 m spans and loads used in both the function of the bridge. For highway bridge, loads are grouped into three, which are self weight girder, additional dead load and live load. The additional dead loads for highway bridge are plate, deck slab, asphalt, and the diaphragm, while for the live load is load D which consists of a Uniform Distributed Load (UDL) and Knife Edge Load (KEL) based on